2016
DOI: 10.18178/jolst.4.2.79-83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and pH on Deinking of Laser-Jet Waste Paper Using Commercial Lipase and Esterase

Abstract: Waste paper recycling has increased dramatically in recent times, and will continue to do so in the foreseeable future. Ink removal constitutes one barrier to converting this raw material into quality products. Enzymatic deinking represents one approach to lowering this barrier. Enzymatic processing, offers potential opportunities for changing the pulp & paper industry towards more environmentally friendly and efficient operations compared to conventional methods. The study addresses two (2) commercial enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…After the films have been fabricated, the CNFs embed into the reduced graphene oxide (RGO) nanosheets to restrain their accumulation. In addition, the hydrophilicity, porosity, and hydroexpansivity of CNFs may be propitious to offer enough diffusion channels for the electrolyte solution and to enhance the contact between electrodes and electrolytes, which may reduce the internal resistance and charge transfer obstruction [34][35][36][37]. In return, the electrochemical performance of the RGO is greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…After the films have been fabricated, the CNFs embed into the reduced graphene oxide (RGO) nanosheets to restrain their accumulation. In addition, the hydrophilicity, porosity, and hydroexpansivity of CNFs may be propitious to offer enough diffusion channels for the electrolyte solution and to enhance the contact between electrodes and electrolytes, which may reduce the internal resistance and charge transfer obstruction [34][35][36][37]. In return, the electrochemical performance of the RGO is greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…It requires good electrochemical performance and flexibility especially for preparing a high-performance flexible supercapacitor. Him et al [ 261 ] and Zhe et al [ 262 ] found that graphene and nanocellulose are excellent flexible electrode materials for supercapacitors. Nanocellulose has been used as a substrate material because of its good biodegradability, mechanical strength, flexibility, and chemical reactivity.…”
Section: Applicationsmentioning
confidence: 99%
“…This is because nanocellulose can provide an effective way for ion transport. The high pore structure and hydrophilic properties of nanocellulose make it easier to transport electrolyte ion [ 261 ].…”
Section: Applicationsmentioning
confidence: 99%